Bridging the Gap: An Assessment and Intervention for Pediatric Providers on the Prevention of Perinatal Transmission of HIV. (4th October 2017) - Jones, Milissa; Ottolini, Martin; Eberly, Matthew
Abstract: Background: In the US, the rates of perinatal transmission of HIV have fallen dramatically since the start of the epidemic. The declining rates have been attributed to key interventions, which pediatric providers should be familiar. Annually, very few mothers infected with HIV give birth at our institution. Such limited exposure may affect our pediatric providers' ability to stay aware of current guidelines as well as maintain their comfort level when caring for infants born to HIV positive mothers. We sought to assess both the level of knowledge of the current guidelines to prevent perinatal transmission of HIV, as well as the comfort level pediatrics providers had with the care of these infants. Methods: Pediatric nurses, staff and trainees, were invited to attend a lecture. Prior to the lecture, a pretest was administered which highlighted the key preventative interventions. Comfort level was also assessed on a 1 to 4 sca1e, 1 denoted "very uncomfortable" and 4 denoted "very comfortable." A 30 minute lecture was conducted which emphasized the vital intervention strategies. A posttest was given following the lecture. In addition, a poster was created summarizing the key preventative interventions and displayed in all neonatal provider areas. Approximately two months following the lecture, an electronic questionnaire was administered to assess knowledge retention. Results: A total of 35 participants completed both the pre and posttest (Figure1). The average score on the pretest was 65.7% and average comfort level 1.94. After the lecture, the average score on the posttest was 98.3% [t(68) =10.63, P =<0.0001] and the average comfort level was 3.00 [t(68) =5.27, P =<0.0001] (Figure 2, 3). A total of 14 participants completed the follow up questionnaire with an average score of 80% and comfort level of 2.3. Conclusion: Limited exposure to mothers delivering with HIV affects both the knowledge and the comfort level of the pediatric providers. We were able to see a significant improvement in the knowledge and comfort level of participants immediately following our intervention. Based on the two month follow up scores, it is evident recurring educational interventions are needed to help sustain these results. Disclosures: All authors: No reported disclosures.